Differential and Independent Roles of a ς(32) Homolog (RpoH) and an HrcA Repressor in the Heat Shock Response of Agrobacterium tumefaciens - Nakahigashi, Kenji (American Society for Microbiology, 1999)
The heat shock response in alpha proteobacteria is unique in that a combination of two regulators is involved: a positive regulator, RpoH (ς(32) homolog), found in the alpha, beta, and gamma proteobacteria, and a negative regulator, HrcA, widely distributed in eubacteria but not in the gamma proteobacteria. To assess the differential roles of the two regulators in these bacteria, we cloned the hrcA-grpE operon of Agrobacterium tumefaciens, analyzed its transcription, and constructed deletion mutants lacking RpoH and/or HrcA. The ΔrpoH mutant and ΔrpoH ΔhrcA double mutant were unable to grow above 30°C. Whereas the synthesis of heat shock proteins (e.g., DnaK, GroEL, and ClpB) was transiently induced upon temperature upshift from 25 to 37°C in the wild type, such induction was not observed in the ΔrpoH mutant, except that GroEL synthesis was still partially induced. By contrast, the ΔhrcA mutant grew normally and exhibited essentially normal heat induction except for a higher level of GroEL expression, especially before heat shock. The ΔrpoH ΔhrcA double mutant showed the combined phenotypes of each of the single mutants. The amounts of dnaK and groE transcripts before and after heat shock, as determined by primer extension, were consistent with those of the proteins synthesized. The cellular level of RpoH but not HrcA increased significantly upon heat shock. We conclude that RpoH plays a major and global role in the induction of most heat shock proteins, whereas HrcA plays a restricted role in repressing groE expression under nonstress conditions.